From theory to action: what motivates consumers to purchase IoT sustainable products - Luminița-Ștefania Bozdog; Bogdana Glovațchi; Gabriela Mircea; Grațiela Georgiana Noja; Tomasz Dorożyński; Andrea Imperia (Journal of Business Economics and Management, 2025)
In an era marked by the importance of sustainability and technological integration, this paper explores the drivers behind sustainable consumption in a rapidly evolving market, focusing on Romanian consumer perspectives towards sustainable products driven by the relationship between the circular economy and the Internet of Things (IoT). Leveraging structural equation modelling, we conduct a thorough survey to investigate the roles of shaping purchase behaviors within the context of the circular economy and IoT integration. The findings reveal that while environmental attitudes significantly influence purchase intentions, price sensitivity and perceived value play a crucial role in shaping consumer choices. From a theoretical perspective, this study highlights the interplay between sustainability concerns and market dynamics, contributing to the broader understanding of sustainable purchase behavior. From a managerial perspective, the results provide actionable insights for businesses to design value-aligned strategies, ensuring that sustainable products are both accessible and appealing to a diverse consumer base. This dual focus on theory and practice offers a roadmap for fostering responsible consumption in a competitive marketplace.